ASSESSMENT OF THE INDICATORS OF PHYSICAL TRAINING OF STUDENTS AGED 16-17 YEARS - Muxtorova Xusnidaxon Abdug‘oporovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article provides information about the system of assessing the indicators of physical training of schoolchildren-young people aged 16-17 years. Also expressed are the indicators between the control and experimental groups after the pedagogical experience.